Intelligent IT governance decision-making support framework for a developing country’s public university - Arshad, Yusri; Ahlan, Abdul Rahman; Ajayi, Binyamin (IOS Press, 2014)
Decision support systems (DSS) can be helpful tools in University’s planning and management. Decision support systems can contribute to efficient exchange of information between experts, stakeholders, decision makers and laypeople. However, intelligent Information technology (IT) governance decision support system for public universities is yet to be thoroughly investigated. This is because IT governance (ITG) is just evolving as a new paradigm to take care the stakeholders’ expectations in leveraging IT with business goals. This study explores issues of IT governance and the suggestion for ITG Intelligent decision making support system (IDMSS) in a public university in Malaysia. The interviews and documents were analysed to generate themes. The findings show the need for effective IT governance in the university. This will enable optimal usage of IT resources, which are expected to have an impact on the university’s performance. The findings is aligned to Control Objectives for Information and related Technology (COBIT) framework and then several proposals from extant researches on IDMSS are described to form a basis for an intelligent ITG DMSS framework suitable for adoption in the context of public Institutes of Higher learning in Malaysia.